Metallosupramolecular polymers formed with silver(i) ions in aqueous solution. (8th February 2022) - Li, Chenxing; Ok, Mirae; Choi, Heekyoung; Jung, Jong Hwa
Abstract : Supramolecular polymers of a terpyridine-based ligand (L ) at three different concentrations of AgNO3 (0, 0.5, and 1.0 equiv.). Abstract : We report supramolecular polymers of a terpyridine-based ligand with an alanine moiety (L ) at three different concentrations of AgNO3 (0, 0.5, and 1.0 equiv.) in a mixture of H2 O and dimethyl sulfoxide (DMSO) (1 : 1 v/v). The self-assembled L obtained without AgNO3 shows a positive circular dichroism (CD) signal indicating right-handed ( P -helicity) helicity. In contrast, the self-assembled L formed in the presence of 0.5 and 1.0 equiv. of AgNO3 shows a negative CD signal indicating left-handed ( M -helicity) helicity.